Proceedings of the Ocean Drilling Program 2006
DOI: 10.2973/odp.proc.sr.202.211.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene Changes in Tropical East Pacific Upper Ocean Stratification: Response to Tropical Gateways?

Abstract: A combination of stable isotope records and Mg/Ca temperature estimates of four different planktonic foraminiferal species from Ocean Drilling Program Site 1241 allows differentiation between temperature and salinity changes in the tropical east Pacific (TEP) upper water column during the Pliocene (~5.7-2.1 Ma). The deviation of δ 18 O records and Mg/Ca temperature estimates from thermocline-dwelling planktonic foraminifers suggests that local changes in salinity exerted a much stronger control on Pliocene TEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
101
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(116 citation statements)
references
References 99 publications
(190 reference statements)
11
101
2
Order By: Relevance
“…As a consequence, small changes in its depth through east-west tilting regulated by short-term climate phenomena such as the El Niño-Southern Oscillation can affect surface-water properties and ocean-atmosphere exchange processes (Fedorov et al, 2004;Ma et al, 2013). In general, proxy records and modeling results consistently document a long-term shoaling of the thermocline in the EEP and other (sub-)tropical upwelling regions throughout the Plio-Pleistocene (Wara et al, 2005;Fedorov et al, 2006;Steph et al, 2006aSteph et al, , 2010Dekens et al, 2007;Ford et al, 2012). However, the dynamics of the thermocline in the EEP and its potential links to the iNHG currently remained enigmatic.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…As a consequence, small changes in its depth through east-west tilting regulated by short-term climate phenomena such as the El Niño-Southern Oscillation can affect surface-water properties and ocean-atmosphere exchange processes (Fedorov et al, 2004;Ma et al, 2013). In general, proxy records and modeling results consistently document a long-term shoaling of the thermocline in the EEP and other (sub-)tropical upwelling regions throughout the Plio-Pleistocene (Wara et al, 2005;Fedorov et al, 2006;Steph et al, 2006aSteph et al, , 2010Dekens et al, 2007;Ford et al, 2012). However, the dynamics of the thermocline in the EEP and its potential links to the iNHG currently remained enigmatic.…”
Section: Introductionmentioning
confidence: 60%
“…The timing led to the hypothesis that thermocline shoaling and the development of the EEP "cold tongue" (Wyrtki, 1981) were necessary preconditions for the iNHG, as they reduced poleward atmospheric heat transport (Cane and Molnar, 2001). However, other studies only identified fundamental shifts in the thermocline depth prior to ∼ 3.5 Ma (Wara et al, 2005;Steph et al, 2006aSteph et al, , 2010Ford et al, 2012), which would imply that the thermocline depth in the EEP did not play an important role in the development of large-scale glaciation in the Northern Hemisphere. In light of these contradictory views, and to ultimately shed new light on potential links between low-latitude thermocline dynamics and high-latitude ice-sheet buildup, we investigated thermocline state changes for Ocean Drilling Program (ODP) Site 849 in the EEP during the final phase of the late Pliocene/early Pleistocene iNHG (∼ 2.75 to 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the eastern equatorial Pacific, subsurface temperatures steeply cooled by ~3°C between 4.0 and 4.8 Ma and gradually cooled an additional ~2°C toward the present day (Ford et al, 2012;Steph et al, 2006Steph et al, , 2010. In comparison, subsurface temperatures gradually cooled ~3°C from the Pliocene to the present day (Ford et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Western Pacific Warm Pool is characterized by warm sea-surface temperatures and a deep thermocline. During the Pliocene warm period (~3 to 5 Ma), subsurface temperatures were warm across the equatorial Pacific, suggesting the tropical thermocline was warm and/or deep (Ford et al, 2012(Ford et al, , 2015Steph et al, 2006Steph et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%